2007
DOI: 10.1111/j.1365-2672.2007.03400.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal bacteria and ageing

Abstract: Summary Advancements in science and medicine, as well as improved living standards, have led to a steady increase in life expectancy, and subsequently a rise in the elderly population. The intestinal microbiota is important for maintenance of host health, providing energy, nutrients and protection against invading organisms. Although the colonic microbiota is relatively stable throughout adult life, age‐related changes in the gastrointestinal (GI) tract, as well as changes in diet and host immune system reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
225
2
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(247 citation statements)
references
References 81 publications
9
225
2
11
Order By: Relevance
“…With regard to other relevant intestinal microbial populations such as the phylum Bacteriodetes, the results are more variable, with some studies reporting lower levels 19,[23][24][25][26][27] while others have indicated increases of this microbial group in elderly subjects. 21 Similarly, variable results have also been observed for lactobacilli, with some studies reporting a reduction 22,28 and others an increase in the levels of these microorganisms at older ages. 24,27,29 It is still unclear whether this variability in the results obtained for certain microbial groups is related to actual population differences or to methodological issues, such as the different techniques used for determining microbial abundancies ( Table 1).…”
Section: The Gut Microbiome: Composition Functionality and Evolutionmentioning
confidence: 95%
“…With regard to other relevant intestinal microbial populations such as the phylum Bacteriodetes, the results are more variable, with some studies reporting lower levels 19,[23][24][25][26][27] while others have indicated increases of this microbial group in elderly subjects. 21 Similarly, variable results have also been observed for lactobacilli, with some studies reporting a reduction 22,28 and others an increase in the levels of these microorganisms at older ages. 24,27,29 It is still unclear whether this variability in the results obtained for certain microbial groups is related to actual population differences or to methodological issues, such as the different techniques used for determining microbial abundancies ( Table 1).…”
Section: The Gut Microbiome: Composition Functionality and Evolutionmentioning
confidence: 95%
“…In elderly persons, the content of bifidobacteria decreases, whereas that of enterobacteria and clostridia increases (Hopkins and MacFarlane, 2002;Woodmansey, 2007). It might, therefore, be expected that in elderly, the bifidogenic effects of inulin could be more pronounced.…”
Section: Elderly Peoplementioning
confidence: 99%
“…The gut microbiota composition of elderly subjects is expected to be in a state of flux, a theory supported by culture-dependent methods (29). More recent studies have suggested that the Bacteroides species diversity was marginally increased in the feces of elderly subjects and that of bifidobacteria reduced (30), whereas a further study suggested that both Bacteroides numbers and species diversity decline in the elderly (31,32). The proportions of the phyla Firmicutes, Bacteroidetes, and Proteobacteria were 58%, 15%, and 27%, respectively (33) in three elderly subjects in Japan, using 16S rRNA gene-clone library sequencing.…”
mentioning
confidence: 99%